Simultaneous effects of multi-walled carbon nanotubes and copper oxide nanoparticles on the rheological behavior of cooling oil: Application for refrigeration systems. (August 2019) - Esfe, Mohammad Hemmat; Dalir, Ramin; Bakhtiari, Reza; Afrand, Masoud
Highlights: Experimental study on rheological behavior of MWCNT-CuO/SAE50 nanolubricant. Measuring viscosity at several concentrations, temperatures and the shear rates. The highest viscosity reduction (−15%) occurred in a volume fraction of 0.0625%. A comparison was performed between the viscosities of different nanofluids. The viscosity sensitivity analysis for temperature and volume fraction has been performed. Abstract: This study discussed the rheological behavior of MWCNT-CuO(30–70%)/SAE50 nanofluid experimentally at the volume fractions of 0–1 percent in the temperature range of 25–50 °C and the shear rate of 666–7998 s -1 . Due to a nonlinear relationship between the shear rate and shear stress, nanofluid behavior can be considered close to the non-Newtonian fluids. Nanofluid viscosity reduces by adding nanoparticles at the volume fractions of 0.0625%, 0.125%, and 0.25% (maximum reduction of 15%). Nanofluid viscosity increases at the volume fractions higher than 0.5%, as the maximum viscosity increase, i.e. 14%, occurs at the volume fraction of 1%. Reduction of viscosity at low volume fractions and a small increase of viscosity at higher volume fractions show that this nanofluid can be used in the applications other than lubrication. This study presents for the first time a new mathematical relation for the relative viscosity of MWCNT-CuO(3–70%)/SAE50. In the relation provided to predict the relative viscosity of nanofluid, R 2 = 0.9453, which indicates its accuracy. This study also discussed the sensitivity of the relative viscosity of nanofluid to temperature and volume fraction.